TRENDS IN THE DEVELOPMENT OF INTERNATIONAL COOPERATION IN MANAGING INVESTMENT PROCESSES IN CENTRAL ASIA: AN ANALYSIS OF THE ‘ONE BELT, ONE ROAD’ INITIATIVE - Habibjonov Usmonjon Sherzodovich (New modern researchers: modern proposals and solutions, 2025)
The study analyzes the main trends in the development of international cooperation in managing investment processes in Central Asia, focusing on the “One Belt, One Road” initiative as a strategic framework for regional economic integration. It explores the mechanisms of attracting foreign direct investment (FDI), institutional reforms, and the role of infrastructure connectivity projects in enhancing investment efficiency across the region. The research identifies how China’s Belt and Road Initiative fosters sustainable industrial growth, cross-border trade, and digital transformation within Central Asian economies. Special attention is given to the challenges of coordination among participating states, the diversification of investment flows, and the formation of new governance models for regional economic partnerships. The findings emphasize the importance of strategic planning, policy harmonization, and technology-driven management in achieving long-term economic resilience and regional competitiveness.